Relationships between abiotic and biotic variables in a maturation pond and their influence on E. coli removal - Ana M. M. Batista (IWA Publishing, 2021)
The effects of depth and climate seasonality on zooplankton, algal biomass, coliforms and Escherichia coli in a small full-scale shallow maturation pond receiving pre-treated domestic wastewater were evaluated during a tropical climatic seasonal cycle. The experiment revealed that the zooplankton community was dominated by rotifers and protozoans, and concentrations were influenced by seasonality. A negative correlation between zooplankton, and pH, dissolved oxygen, temperature and ultraviolet radiation, and chlorophyll-a and Escherichia coli were observed at all depths. The major driving forces influencing Escherichia coli were pH, dissolved oxygen, ultraviolet radiation and the zooplankton. A significant difference between Escherichia coli removal throughout the three different depths were observed. Both bacterial and zooplankton concentrations were greater closer to the bottom of the pond, therefore reinforcing the integral role of solar radiation on bacterial removal. These results give an insight on the dynamics of these groups in pond systems treating domestic wastewater, by correlating the variation of zooplankton with biotic and abiotic variables and seasonal changes in a tropical climate, where few studies have been performed on this topic. HIGHLIGHTS The variables pH, DO, zooplankton community and solar radiation are shown to be determining factors in reducing E. coli in a maturation pond.; Zooplankton concentrations were greater closer to the bottom of the pond.; E. coli removal varied between the three different depths reinforcing the role of solar radiation on bacterial removal rate.;